IMPLEMENTASI METODE RATING SCALE PADA SISTEM ABSENSI ONLINE SEBAGAI PENUNJANG PENILAIAN KINERJA PEGAWAI (STUDI KASUS : PANDA LOVELY JOMBANG) - Muhammad Toha; Ginanjar Setyo Permadi; Ahmad Heru Mujianto; Terdy Kistofer (Fakultas Teknologi Informasi, 2025)
Attendance is often used as a consideration for a superior to assess employee performance. Attendance data is very influential in seeing and assessing employee absenteeism. Attendance that still uses paper tends to have many weaknesses, including data loss, data errors or damage to attendance data. Online attendance is attendance that uses web-based technology that can help employees with attendance and superiors can see and assess an employee's performance. This online attendance was built using Mysql as a database system and framework called Laravel. The system uses email and passwords as data security and this system is equipped with several menu features including an attendance menu, which displays employee entry and return data with the time and date the employee was absent, an attendance history menu for both users to avoid data errors as well as data backup material, the result is that employees do not need to worry about data loss, data errors or data damage. The system also applies a rating scalemethod, where the system can display employee attendance data in a display of the lowest scale value to the highest value, through this system superiors can make considerations regarding an employee's performance. Keywords: Attendance, Online Attendance, Mysql, Laravel, rating scale.